Mind the knowledge gap!: The origins of declining business dynamism in a macro agent-based model - Domenico Delli Gatti; Roberta Terranova; Enrico Turco (Università Cattolica del Sacro Cuore, Dipartimento di Economia e Finanza (DISCE), 2023)
In this paper we replicate most of the stylized facts characterizing the decline in business dynamism in the USA highlighted by Akcigit and Ates (2021) and provide an explanation of their emergence by means of a macroeconomic agent-based model populated by two types of firms: innovators who generate new and more productive capital goods, and entrepreneurs who employ labor and capital goods to produce consumption goods. A key ingredient of the model is the assumption that the entrepreneurs' access to new and better capital goods depends on the knowledge gap, i.e., the wedge between the firm's technical knowledge and the state of technology embodied in new capital goods. Within this framework, we investigate the obstacles to knowledge diffusion subsequently leading to declining business dynamism. Our findings indicate that the dissipation of knowledge leads to high market concentration and markups, falling labor share and decelerating productivity only when knowledge diffusion decreases both in technology imitation among innovators and in technology adoption by entrepreneurs. Patents are an important obstacle to knowledge diffusion. We find an inverse U-shaped relationship between patent strength and growth: moderate levels of patent protection can stimulate growth, but strong protection leads to rising market power and slower growth.
Keywords: O31; O32; O33; O34; 330; Innovation; Imitation; Knowledge diffusion; Knowledge gap; Patents